Reflective Practice Strategies of English Language Teachers in Education (Journal of Vishwa Adarsha College, 2025)
Reflective practice has gained recognition as a key component in improving teaching effectiveness and fostering continuous professional growth among educators. This study aimed to explore the reflective practice strategies used by English teachers and examine the role of reflection in uncovering the reality of their teaching experiences. Using a qualitative approach with a phenomenological design, the research involved in-depth interviews with eight purposively selected English teachers from the Kathmandu district. The study found that reflective practice strategies, such as sharing experiences, participating in discussions, critical thinking, creative writing, maintaining diaries, peer observation, and team teaching, significantly enhanced teaching skills and improve teaching learning. These strategies activated and enriched the classroom environment, fostering critical thinking and creativity. Additionally, the study highlighted that reflection contributed to teachers' professional development and learning, suggesting that incorporating reflective practices into teacher training programs could improve teaching effectiveness and overall educational quality. The findings emphasize the value of reflective practices in continuous professional growth and enhancing individual and collective teaching experiences.